2020
DOI: 10.1111/ejn.14669
|View full text |Cite
|
Sign up to set email alerts
|

Network and cellular mechanisms underlying heterogeneous excitatory/inhibitory balanced states

Abstract: Recent work has explored spatiotemporal relationships between excitatory (E) and inhibitory (I) signaling within neural networks, and the effect of these relationships on network activity patterns. Data from these studies have indicated that excitation and inhibition are maintained at a similar level across long time periods and that excitatory and inhibitory currents may be tightly synchronized. Disruption of this balance—leading to an aberrant E/I ratio—is implicated in various brain pathologies. However, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
2
3
0
Order By: Relevance
“…These last two regimes are independent of neural resonance properties but only depend on structural network properties, coinciding with previous results observed in similar networks consisting of type 1 neurons (Wu et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These last two regimes are independent of neural resonance properties but only depend on structural network properties, coinciding with previous results observed in similar networks consisting of type 1 neurons (Wu et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…The networks contained equal numbers of E and I cells so that the relative contributions of excitatory and inhibitory signaling in the network could be directly compared and controlled by the relative values of the synaptic strengths, w E and w I . In most brain networks, E cells outnumber I cells with a ratio of about 10:1, and we have previously shown that qualitatively similar E/I regulation occurs in networks with more physiologically accurate fractions of cell types (Wu, Aton et al, 2020). Additionally, the networks considered here had a fixed connectivity density (3%) that is within the range of reported estimates for local connectivity in hippocampal brain areas, but higher than the reported median (Tecuatl et al, 2021).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Here, we define brain homeostasis as the mechanisms that would either strengthen or weaken activity that is respectively above or below what is necessary to maintain baseline function and activity balance at either a local or network level. While homeostatic control of neuronal activity at the cellular level has been widely investigated in the last two decades [9,10], the study of biological mechanisms underlying homeostatic control of neural network function is receiving attention only more recently [11][12][13]. In this context, development, deprivation and activity-dependent plasticity constitute real challenges to maintaining balance within the sensorimotor system, without over-constraining plasticity that is vital for adaptive changes.…”
Section: Balancing Between Plasticity and Stabilitymentioning
confidence: 99%
“…Multiple synaptic or circuit-level factors establish and tightly regulate neuronal E/I balance ( 163 ). The balance between excitatory and inhibitory synapses in the brain is maintained through a complex interplay of several factors.…”
Section: What Role Does the Rodent Pfc Play During Social Interactions?mentioning
confidence: 99%